Relationship between Knowledge and Patient Attitude in Preventing Complications of Diabetes Mellitus Foot Wounds - Danisa Bella Syaharani; Supratman Supratman (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes mellitus is a disease that can cause serious complications, including foot wounds which can lead to diabetes mellitus and amputation. Therefore, the aim of this research is to determine the relationship between knowledge and patient attitudes in preventing complications of diabetes mellitus at the Kartasura Community Health Center, Sukoharjo Regency. The instrument used in this research was a structural questionnaire to measure the patient's level of knowledge and attitudes with validity and reliability values of 0.621-0.633. Respondents in the study involving patients diagnosed with diabetes mellitus and currently undergoing treatment at the Kartasura Health Center, totaling 70 respondents, used a purposive sampling technique. This research shows that there is a relationship between the level of knowledge and attitudes of patients in preventing complications of foot wounds due to diabetes mellitus, with a significant parameter value (p-value) = (0.04) which shows a fairly strong correlation with an r value of 0.342. By using the Spearman Rho test, the results of research conducted by researchers show that there is a relationship between knowledge and patient attitudes in preventing complications of diabetes mellitus foot wounds. In conclusion, the higher the patient's knowledge, the more positive the patient's attitude is in implementing preventive measures against complications of foot wounds due to diabetes mellitus.